WOOD MODIFICATION: AN UPDATE - Callum A. S. Hill (BioResources, 2011)
Wood modification is a generic term describing the application of chemical, physical, or biological methods to alter the properties of the material. The aim is to get better performance from the wood, resulting in improvements in dimensional stability, decay resistance, weathering resistance, etc. It is essential that the modified wood is non-toxic in service and that disposal at the end of life does not result in the generation of any toxic residues. Over the past five years there have been significant developments in wood modification technologies, especially in the commercial sector. This technology is here to stay.